Effects of case characteristics on teamwork in family meetings. Issue 4 (11th December 2018) - Kim, Jangmin; Imburgia, Teresa M.; Armstrong‐Richardson, Eprise; Jaggers, Jeremiah W.; Hall, James A.
Abstract: Little empirical research has examined the effects of case characteristics on high‐quality teamwork within family meetings in child welfare. We attempted to fill this gap using 497 child welfare cases in a Midwestern state in the United States. We found that overall teamwork was negatively associated with domestic violence, frequent placement moves, and a permanency plan of adoption, whereas teamwork was positively associated with the length of involvement in the child welfare system. We also examined the relationships between the case characteristics and two components of teamwork. The results showed that domestic violence and the length of the involvement were equally significant factors for both team formation and functioning. The permanency plan of adoption was a significant factor for team formation, but not for team functioning. Finally, family voices and frequent team meetings appeared to be stronger factors for improving both team formation and functioning. The results suggest that families in the child welfare system have different experiences in forming and functioning high‐quality family team meetings. Therefore, it is necessary to customize specific processes and strategies to promote teamwork depending on the child and family's characteristics and situations.